الجملة الإنشائية في اللغتين العربية والإندونيسية في ضوء التحليل التقابلي (الاستفهام مثالاً): Structural Sentences in Arabic and Indonesian Viewed from Comparative Analysis (Inquiry Sentences as Examples) - Rustam Koly (البصيرة: مجلة الدراسات الإسلامية, 2023)
The purpose of this study is to find out the forms and functions of interrogative sentences in Arabic and Indonesian, discuss the similarities and differences between the two languages, and explain the methods used in both languages. This study also aims to contribute to overcoming language difficulties and errors that are often experienced by Indonesian students when learning Arabic, especially in the form of interrogative sentences. The method used in this study is a descriptive method of comparison between the two languages, which consists of three stages: (1) description of the language of inquiry in both languages, (2) discovery of similarities and differences between the two languages, and (3) prediction of possible difficulties experienced by Indonesians in learning Arabic. Some of the results of this study are: (1) there are several similarities in the use of interrogative tools in Arabic and Indonesian, whether original or not, singular or plural, and both languages ​​have an important role in the form of interrogative sentences; (2) the word order in the use of question tools and interrogative sentences between Arabic and Indonesian is almost the same, and the two have a close relationship; and (3) the time in interrogative sentences in both languages, which can be used to ask about the past, present, or future. However, there are some differences in the form of interrogative sentences between Arabic and Indonesian, such as: (1) in Arabic, interrogative sentences are used to ask for confirmation and descriptions, whereas in Indonesian, interrogative sentences are only used to ask for descriptions; (2) in Arabic, interrogative sentences are carried out using a questioning tool and emphasis on voice, whereas in Indonesian, interrogative sentences can be carried out in three ways, namely only voice emphasis, using question tools and voice stress, and using question tools, voice stress. , and affixes. These differences can be difficult for Indonesians learning Arabic.